Prevalencia de enteroparásitos en embarazadas de la maternidad "Dr. Armando Castillo Plaza" en Maracaibo, Venezuela - Acurero O Ellen; Díaz A Iris; Díaz A Nelly; Bracho M Angela; Ferrer H María; Matheus M Alberto (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
Abstract: For to determine the prevalence of intestinal parasites in pregnant women between 14 and 43 years old at Dr Armando Castillo Plaza maternity center in Maracaibo Municipality. 120 stool samples were obtained and analyzed by copro-parasitical methods such as fresh test with saline solution and lugol, and concentration techniques with formaldehyde - eter (Ritchie); Kinyoun coloration for the diagnosis of intestinal coccidias. Kato Katz method was performed demonstrating the geohelminthiasis severity. Parasite infestation prevalence was found in 65.9% and the most affected age group was the one between 23 and 31 years (48.1 %), with protozoal predominance (86%) over helminth (14%). The principal parasitical species found were B. hominis (48.3%), E. nana (25%), E. coli, E. histolytica / E. dispar complex (13.3%), T. trichiura (4.2%), A. lumbricoides (3.3%), S. stercoralis (1.6%), Ancylostomideos, Taenia sp. (0.8%). No intestinal coccidias were found in any of the analysis did not demonstrate any significance between the variables parasitism group by age, parasitism - pregnancy state and parasitism - anemia. The studied pregnant population is susceptible to be infested by intestinal parasites. Resumen: Para determinar la prevalencia de parásitos intestinales en gestantes con edades comprendidas entre 14 y 43 años de la Maternidad Dr. Armando Castillo Plaza del Municipio Maracaibo, Venezuela; se analizaron 120 muestras fecales, a las cuales se les practicó métodos coproparasitológicos mediante examen al fresco con SSF y coloraciones temporales de lugol y nair, técnicas de concentración de formol - éter, coloración de Kinyoun para el diagnóstico de coccidios intestinales y técnica de recuento de huevos (Kato-Katz) para determinar la severidad de las Geohelmintiasis. Se encontró una prevalencia de infestación parasitaria en un 65,9% y el grupo etario más afectado fue el de 23 a 31 años (48,1%). Las principales especies parasitarias encontradas fueron B. hominis (48,3%), E. nana (25%), E. coli, complejo E. histolytica/E. dispar (13,3%), T. trichiura (4,2%). A. lumbricoides (3,3%), S. stercoralis (1,6%), Ancylostomideos y Taenia sp. (0,8%). No se detectó la presencia de coccidios intestinales. El análisis estadístico de Ji cuadrado (x2) no mostró significancia entre las variables parasitismo - edad gestacional, parasitismo -grupo etario, parasitismo - anemia. La población de gestantes estudiadas es susceptible a las infestaciones por parasitosis intestinales.